Composite flame retardant for cable material and preparation method thereof
By using pretreated parallolite clay and hexagonal boron nitride in polyethylene cable material, combined with electron beam irradiation crosslinking, the problem of poor flame retardancy of polyethylene cable material is solved, and mechanical properties and thermal conductivity are improved Performance extends the service life of cable materials.
Patent Information
- Application Number
- CN202411390475.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-08
AI Technical Summary
The flame retardant and thermal conductivity of polyethylene cable materials are poor, which leads to flammable fire and threatens life safety. The large amount of add of stalletite clay will reduce the mechanical properties of the cable materials.
Using composite flame retardant, the coordinated structure of activated clay and boron nitride is formed by pretreating the palyite clay and combining with hyperbranched polyamide amine and hydroxylation of hexagonal boron nitride to form a synergistic structure of activated clay and boron nitride, improving flame retardant performance and thermal conductivity and promote heat transfer by electron beam irradiation crosslinking.
It significantly improves the mechanical properties and flame retardant properties of polyethylene cable materials, extends the service life of cable materials, and ensures the mechanical strength and thermal conductivity of the products.
Smart Images

Figure CN119286062A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cable flame retardants, and in particular to a composite flame retardant for cable materials and a preparation method thereof. Background Art
[0002] Plastics used for insulation and sheathing of wires and cables are commonly known as cable materials, which are mainly composed of polymer base materials and additives. For polymers that can be used in the field of wires and cables, they are not only required to have good electrical insulation properties and good processing properties, but also good flame retardant properties. Flame retardant wires and cables can greatly reduce casualties and property losses caused by fires caused by wires and cables.
[0003] Polyethylene has the advantages of good electrical insulation, small dielectric constant, low dielectric loss and excellent chemical stability, and is one of the widely used polymer base materials in cable materials. However, polyethylene has poor flame retardancy and thermal conductivity, with an oxygen index of only 17.4 and a thermal conductivity of only 0.3-0.5W / (m·K). Therefore, it is very easy to burn under uneven heating or external environmental influences, and is not easy to extinguish, posing a huge threat to people's life safety, resulting in limited development in the field of cable materials.
[0004] Fire statistics show that fires caused by wires and cables have become more frequent in recent years, and the flame retardancy of cable materials is very important. Therefore, the development of high thermal conductivity flame retardants for polyethylene has a significant role in promoting the development of the wire and cable industry.
[0005] Palygorskite clay is a natural hydrated magnesium aluminum silicate mineral with a special rod-shaped and needle-shaped crystal structure. Palygorskite clay has excellent decolorization, adsorption, ion exchange, thermal stability, salt resistance, gelation and high-temperature phase change properties. It has a wide range of uses and can be widely used in petroleum, chemical industry, building materials, papermaking, medicine, agriculture, ecological environment protection, leather making, feed, fertilizer, food, automobile and military industry. The application of palygorskite clay in flame retardant materials has received widespread attention in recent years. The compound of palygorskite clay and boron nitride flame retardant has excellent flame retardant properties, but the addition amount is limited. If a large amount is added, it can improve the flame retardancy of the material, but it will cause the mechanical properties of polyethylene cable materials to be significantly reduced, which needs to be solved urgently. Summary of the invention
[0006] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a composite flame retardant for cable materials and a preparation method thereof.
[0007] A composite flame retardant for cable materials. The raw materials thereof include, by mass, 10-20 parts of palygorskite clay, 1-2 parts of gamma-aminopropyltriethoxysilane, 1.01-3.1 parts of sodium methoxide, 1-5 parts of ethylenediamine, 5-10 parts of methyl acrylate, 1.5-6 parts of glyoxylic acid, 1-2 parts of potassium ethoxide and 5-15 parts of hexagonal boron nitride.
[0008] Preferably, the particle size of hexagonal boron nitride is 100-300 nm.
[0009] The preparation method of the composite flame retardant for cable materials comprises the following steps:
[0010] S1. Add palygorskite clay to deionized water and stir for 10-20 min, perform ultrasonic grinding for 1-4 h, add γ-aminopropyltriethoxysilane, stir at 85-95° C. for 1-2 h, cool to room temperature, filter, and vacuum dry to obtain pretreated clay;
[0011] S2, adding the pretreated clay to methanol and stirring evenly, adding potassium methoxide and stirring evenly, adding ethylenediamine and methyl acrylate in sequence under nitrogen protection, stirring at 10-20° C. for 20-30 hours under nitrogen protection, heating to 30-40° C. and stirring for 5-15 hours, removing nitrogen protection, adding glyoxylic acid solution, stirring at 10-20° C. for 1-2 hours, centrifuging, washing, and vacuum drying to obtain activated clay;
[0012] S3. Mix and grind sodium methoxide and potassium ethoxide evenly, add hexagonal boron nitride, react at 180-190°C with stirring for 1-2h, cool to room temperature, wash, dry, add to ethanol aqueous solution with activated clay, reflux at 100-120°C with stirring for 1-2h, cool to room temperature, centrifuge, and dry in vacuo.
[0013] Preferably, in S1, the ultrasonic pulverization treatment power is 800-1000W.
[0014] Preferably, in S2, the mass fraction of the glyoxylic acid solution is 30-40%.
[0015] Preferably, the mass ratio of potassium methoxide used in S2 to potassium methoxide used in S3 is 0.01-0.1:1-3.
[0016] Preferably, in S3, the mass fraction of the ethanol aqueous solution is 50-70%.
[0017] A flame retardant cable material, the raw materials of which include: the composite flame retardant for cable material and polyethylene.
[0018] Preferably, the raw materials of the flame retardant cable material include, by mass: 100 parts of polyethylene, 1-3 parts of toughening agent, and 20-30 parts of composite flame retardant for the cable material.
[0019] The preparation method of the flame-retardant cable material comprises the following steps: uniformly mixing polyethylene, a toughening agent and the composite flame retardant for the cable material, refining at 130-150°C for 1-5 minutes, melting, plasticizing and molding at 190-210°C for 1-5 minutes, the plasticizing pressure is 20-30MPa, and cross-linking is performed by electron beam irradiation with an irradiation dose of 150-160kGy.
[0020] Beneficial effects:
[0021] If the palygorskite clay is directly added to the polyethylene matrix, the dispersibility is poor. In the present invention, the palygorskite clay is pretreated and then combined with a hyperbranched polyamide amine on its surface, which not only greatly enhances the dispersibility of the palygorskite clay in the polyethylene matrix, but also the end is carboxylated by glyoxylic acid treatment, and the hyperbranched polyamide amine has a unique cavity structure and a three-dimensional structure, which is more conducive to the isotropic uniformity of the palygorskite clay in the polyethylene matrix. In addition, the palygorskite clay can overlap in the polyethylene matrix to form a skeleton and promote the formation of a new network, thereby significantly improving the mechanical properties and flame retardant properties of the polyethylene matrix and improving the durability of the cable material.
[0022] The present invention uses hexagonal boron nitride to undergo hydroxylation treatment, which can effectively increase the reactivity between hexagonal boron nitride and activated clay. The activated clay obtained in the present invention has a large number of carboxyl groups on its surface, which can be combined with the hydroxyl groups on the surface of boron nitride. Not only is the bonding strength high, but also the boron nitride can be evenly combined with the palygorskite clay structure due to its special flaky hexagonal structure. The two work synergistically, improving flame retardancy while also having excellent thermal conductivity.
[0023] The composite flame retardant obtained by the present invention is applied to polyethylene-based cable materials. After being melt-plasticized and then cross-linked by electron beam irradiation, the regular arrangement of boron nitride is effectively promoted, which not only promotes rapid heat transmission and reduces the possibility of heat concentration, but also has high bonding strength with polyethylene, further enhances durability, and effectively prolongs the service life of the cable material.
[0024] The composite flame retardant for cable material obtained by the present invention not only has excellent flame retardancy and thermal conductivity, but also can ensure the mechanical strength of the product when applied to the cable material. At the same time, the method and the required equipment of the present invention are simple, the raw materials and intermediates are inexpensive, and the implementation is convenient. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the thermogravimetric analysis curve of the flame retardant cable material obtained in Example 5.
[0026] Figure 2 It is a comparison chart of the tensile strength and elongation at break of the flame retardant cable materials obtained in Example 5 and Comparative Examples 1-2.
[0027] Figure 3This is a comparison chart of the retention rate of tensile properties of the flame-retardant cable materials obtained in Example 5 and Comparative Examples 1-2 after heat aging (150°C×72h).
[0028] Figure 4 It is a comparison chart of thermal conductivity and oxygen index of the flame retardant cable materials obtained in Example 5 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0029] The present invention will be further explained below in conjunction with specific embodiments.
[0030] The polyolefin thermoplastic elastomer (POE) used below is from ExxonMobil of the United States and has the brand name VM6202.
[0031] Example 1
[0032] A composite flame retardant for cable materials, the raw materials of which include: 1000g of palygorskite clay, 100g of gamma-aminopropyltriethoxysilane, 101g of sodium methoxide, 100g of ethylenediamine, 500g of methyl acrylate, 150g of glyoxylic acid, 100g of potassium ethoxide, and 500g of hexagonal boron nitride with a particle size of 100-300nm.
[0033] The preparation method of the composite flame retardant for cable materials comprises the following steps:
[0034] S1, adding palygorskite clay to 5000g of deionized water, stirring at a speed of 1000r / min for 10min, treating with an ultrasonic pulverizer for 1h, with a processing power of 800W, adding γ-aminopropyltriethoxysilane, stirring at a temperature of 85°C for 1h, cooling to room temperature, filtering, and vacuum drying to obtain pretreated clay;
[0035] S2, adding the pretreated clay to 3000g methanol and stirring evenly, adding 1g potassium methoxide and stirring evenly, adding ethylenediamine and methyl acrylate in sequence under nitrogen protection, stirring at 10°C for 20h under nitrogen protection, heating to 30°C and stirring for 5h, removing nitrogen protection, adding 30% glyoxylic acid solution by mass, stirring at 10°C for 1h, centrifuging, washing with deionized water, and vacuum drying to obtain activated clay;
[0036] S3. Mix and grind 100g of sodium methoxide and potassium ethoxide, add hexagonal boron nitride, react at 180°C with stirring for 1h, cool to room temperature, wash, dry, add them and activated clay to 10000g of 50% ethanol aqueous solution, reflux at 100°C with stirring for 1h, cool to room temperature, centrifuge, and dry in vacuum.
[0037] A flame retardant cable material, the raw materials of which include: 1000g of polyethylene, 10g of polyolefin thermoplastic elastomer, and 200g of a composite flame retardant for the cable material.
[0038] The preparation method of the flame-retardant cable material comprises the following steps: uniformly mixing polyethylene, polyolefin thermoplastic elastomer and the composite flame retardant for the cable material, feeding into a double-roll mill, refining at a temperature of 130°C for 1 minute, melting, plasticizing and molding at a temperature of 190°C for 1 minute, the plasticizing pressure is 20MPa, and electron beam irradiation cross-linking is adopted, and the irradiation dose is 150kGy.
[0039] Example 2
[0040] A composite flame retardant for cable materials, whose raw materials include: 2000g of palygorskite clay, 200g of gamma-aminopropyltriethoxysilane, 310g of sodium methoxide, 500g of ethylenediamine, 1000g of methyl acrylate, 600g of glyoxylic acid, 200g of potassium ethoxide, and 1500g of hexagonal boron nitride with a particle size of 100-300nm.
[0041] The preparation method of the composite flame retardant for cable materials comprises the following steps:
[0042] S1, adding palygorskite clay to 15000g of deionized water, stirring at a speed of 2000r / min for 20min, treating with an ultrasonic pulverizer for 4h, with a processing power of 1000W, adding γ-aminopropyltriethoxysilane, stirring at a temperature of 95°C for 2h, cooling to room temperature, filtering, and vacuum drying to obtain pretreated clay;
[0043] S2, adding the pretreated clay to 5000g of methanol and stirring evenly, adding 10g of potassium methoxide and stirring evenly, adding ethylenediamine and methyl acrylate in sequence under nitrogen protection, stirring at 20°C for 30h under nitrogen protection, heating to 40°C and stirring for 15h, removing nitrogen protection, adding 40% glyoxylic acid solution by mass, stirring at 20°C for 2h, centrifuging, washing with deionized water, and vacuum drying to obtain activated clay;
[0044] S3. Mix and grind 300g of sodium methoxide and potassium ethoxide, add hexagonal boron nitride, react at 190°C with stirring for 2h, cool to room temperature, wash, dry, add them and activated clay to 15000g of 70% ethanol aqueous solution, reflux at 120°C with stirring for 2h, cool to room temperature, centrifuge, and dry in vacuum.
[0045] A flame retardant cable material, the raw materials of which include: 1000g of polyethylene, 30g of polyolefin thermoplastic elastomer, and 300g of a composite flame retardant for the cable material.
[0046] The preparation method of the flame-retardant cable material comprises the following steps: uniformly mixing polyethylene, polyolefin thermoplastic elastomer and the composite flame retardant for the cable material, feeding into a double-roll mill, refining at a temperature of 150°C for 5 minutes, melting, plasticizing and molding at a temperature of 210°C for 5 minutes, the plasticizing pressure is 30MPa, and electron beam irradiation cross-linking is adopted, and the irradiation dose is 160kGy.
[0047] Example 3
[0048] A composite flame retardant for cable materials, whose raw materials include: 1200g of palygorskite clay, 170g of gamma-aminopropyltriethoxysilane, 257g of sodium methoxide, 200g of ethylenediamine, 900g of methyl acrylate, 200g of glyoxylic acid, 170g of potassium ethoxide, and 800g of hexagonal boron nitride with a particle size of 100-300nm.
[0049] The preparation method of the composite flame retardant for cable materials comprises the following steps:
[0050] S1, adding palygorskite clay to 12000g of deionized water, stirring at a speed of 1300r / min for 18min, treating with an ultrasonic pulverizer for 2h, with a processing power of 950W, adding γ-aminopropyltriethoxysilane, stirring at a temperature of 88°C for 100min, cooling to room temperature, filtering, and vacuum drying to obtain pretreated clay;
[0051] S2, adding the pretreated clay to 3500g methanol and stirring evenly, adding 7g potassium methoxide and stirring evenly, adding ethylenediamine and methyl acrylate in sequence under nitrogen protection, stirring at 12°C for 28h under nitrogen protection, heating to 33°C and stirring for 12h, removing nitrogen protection, adding 33% glyoxylic acid solution by mass, stirring at 18°C for 80min, centrifuging, washing with deionized water, and vacuum drying to obtain activated clay;
[0052] S3. Mix and grind 250g of sodium methoxide and potassium ethoxide evenly, add hexagonal boron nitride, react at 182°C with stirring for 100min, cool to room temperature, wash, dry, add them and activated clay to 11000g of 65% ethanol aqueous solution, reflux and stir at 105°C for 100min, cool to room temperature, centrifuge, and dry in vacuum.
[0053] A flame retardant cable material, the raw materials of which include: 1000g of polyethylene, 15g of polyolefin thermoplastic elastomer, and 280g of a composite flame retardant for the cable material.
[0054] The preparation method of the flame-retardant cable material comprises the following steps: uniformly mixing polyethylene, polyolefin thermoplastic elastomer and the composite flame retardant for the cable material, feeding into a double-roll mill, refining at a temperature of 135°C for 4 minutes, melting, plasticizing and molding at a temperature of 195°C for 4 minutes, the plasticizing pressure is 22MPa, and electron beam irradiation cross-linking is adopted, and the irradiation dose is 158kGy.
[0055] Example 4
[0056] A composite flame retardant for cable materials, whose raw materials include: 1800g of palygorskite clay, 130g of gamma-aminopropyltriethoxysilane, 153g of sodium methoxide, 400g of ethylenediamine, 700g of methyl acrylate, 400g of glyoxylic acid, 130g of potassium ethoxide, and 1200g of hexagonal boron nitride with a particle size of 100-300nm.
[0057] The preparation method of the composite flame retardant for cable materials comprises the following steps:
[0058] S1, adding palygorskite clay to 8000g of deionized water, stirring at a speed of 1700r / min for 12min, treating with an ultrasonic pulverizer for 3h, with a processing power of 850W, adding γ-aminopropyltriethoxysilane, stirring at a temperature of 92°C for 80min, cooling to room temperature, filtering, and vacuum drying to obtain pretreated clay;
[0059] S2, adding the pretreated clay to 4500g methanol and stirring evenly, adding 3g potassium methoxide and stirring evenly, adding ethylenediamine and methyl acrylate in sequence under nitrogen protection, stirring at 18°C for 22h under nitrogen protection, heating to 37°C and stirring for 8h, removing nitrogen protection, adding 37% glyoxylic acid solution by mass, stirring at 12°C for 100min, centrifuging, washing with deionized water, and vacuum drying to obtain activated clay;
[0060] S3. Mix and grind 150g of sodium methoxide and potassium ethoxide evenly, add hexagonal boron nitride thereto, react at 188°C with stirring for 80min, cool to room temperature, wash, dry, add them and activated clay to 13000g of 55% ethanol aqueous solution, reflux and stir at 115°C for 80min, cool to room temperature, centrifuge, and dry in vacuo.
[0061] A flame retardant cable material, the raw materials of which include: 1000g of polyethylene, 25g of polyolefin thermoplastic elastomer, and 220g of a composite flame retardant for the cable material.
[0062] The preparation method of the flame-retardant cable material comprises the following steps: uniformly mixing polyethylene, polyolefin thermoplastic elastomer and the composite flame retardant for the cable material, feeding into a double-roll mill, refining at a temperature of 145°C for 2 minutes, melting, plasticizing and molding at a temperature of 205°C for 2 minutes, the plasticizing pressure is 28MPa, and electron beam irradiation cross-linking is adopted, and the irradiation dose is 152kGy.
[0063] Example 5
[0064] A composite flame retardant for cable materials, whose raw materials include: 1500g of palygorskite clay, 150g of gamma-aminopropyltriethoxysilane, 205g of sodium methoxide, 300g of ethylenediamine, 800g of methyl acrylate, 300g of glyoxylic acid, 150g of potassium ethoxide, and 1000g of hexagonal boron nitride with a particle size of 100-300nm.
[0065] The preparation method of the composite flame retardant for cable materials comprises the following steps:
[0066] S1, adding palygorskite clay to 10000g of deionized water, stirring at a speed of 1500r / min for 15min, treating with an ultrasonic pulverizer for 2.5h, the treatment power is 900W, adding γ-aminopropyltriethoxysilane, stirring at a temperature of 90°C for 90min, cooling to room temperature, filtering, and vacuum drying to obtain pretreated clay;
[0067] S2, adding the pretreated clay to 4000g methanol and stirring evenly, adding 5g potassium methoxide and stirring evenly, adding ethylenediamine and methyl acrylate in sequence under nitrogen protection, stirring at 15°C for 25h under nitrogen protection, heating to 35°C and stirring for 10h, removing nitrogen protection, adding 35% glyoxylic acid solution by mass, stirring at 15°C for 90min, centrifuging, washing with deionized water, and vacuum drying to obtain activated clay;
[0068] S3. Mix and grind 200g of sodium methoxide and potassium ethoxide, add hexagonal boron nitride, react at 185°C with stirring for 90min, cool to room temperature, wash, dry, add them and activated clay to 12000g of 60% ethanol aqueous solution, reflux and stir at 110°C for 90min, cool to room temperature, centrifuge, and dry in vacuum.
[0069] A flame retardant cable material, the raw materials of which include: 1000g of polyethylene, 20g of polyolefin thermoplastic elastomer, and 250g of a composite flame retardant for the cable material.
[0070] The preparation method of the flame-retardant cable material comprises the following steps: uniformly mixing polyethylene, polyolefin thermoplastic elastomer and the composite flame retardant for the cable material, feeding into a double-roll mill, refining at a temperature of 140°C for 3 minutes, melting, plasticizing and molding at a temperature of 200°C for 3 minutes, the plasticizing pressure is 25MPa, and electron beam irradiation cross-linking is adopted, and the irradiation dose is 155kGy.
[0071] The flame retardant cable material obtained in this example was subjected to thermogravimetric analysis at 20-600° C. in an oxygen atmosphere with a heating rate of 10° C. / min.
[0072] like Figure 1 As shown, the flame-retardant cable material obtained in this embodiment begins to decompose at 350°C, has a concentrated weight loss range, a sharp endothermic peak and a large amount of endothermic heat, and the decomposed product is difficult to burn, and the combustion is effectively prevented by forming a barrier layer.
[0073] Comparative Example 1
[0074] A composite flame retardant for cable materials, whose raw materials include: 1500g of palygorskite clay, 205g of sodium methoxide, 300g of ethylenediamine, 800g of methyl acrylate, 300g of glyoxylic acid, 150g of potassium ethoxide, and 1000g of hexagonal boron nitride with a particle size of 100-300nm.
[0075] The preparation method of the composite flame retardant for cable materials comprises the following steps:
[0076] S1. Add palygorskite clay to 4000g methanol and stir evenly, add 5g potassium methoxide and stir evenly, add ethylenediamine and methyl acrylate in sequence under nitrogen protection, stir at 15°C for 25h under nitrogen protection, heat to 35°C and stir for 10h, remove nitrogen protection, add 35% glyoxylic acid solution by mass, stir at 15°C for 90min, centrifuge, wash with deionized water, and vacuum dry to obtain activated clay;
[0077] S2. Mix and grind 200g of sodium methoxide and potassium ethoxide, add hexagonal boron nitride, react at 185°C with stirring for 90min, cool to room temperature, wash, dry, add them and activated clay to 12000g of 60% ethanol aqueous solution, reflux and stir at 110°C for 90min, cool to room temperature, centrifuge, and dry in vacuum.
[0078] A flame retardant cable material, the raw materials of which include: 1000g of polyethylene, 20g of polyolefin thermoplastic elastomer, and 250g of a composite flame retardant for the cable material.
[0079] The preparation method of the flame-retardant cable material comprises the following steps: uniformly mixing polyethylene, polyolefin thermoplastic elastomer and the composite flame retardant for the cable material, feeding into a double-roll mill, refining at a temperature of 140°C for 3 minutes, melting, plasticizing and molding at a temperature of 200°C for 3 minutes, the plasticizing pressure is 25MPa, and electron beam irradiation cross-linking is adopted, and the irradiation dose is 155kGy.
[0080] Comparative Example 2
[0081] A composite flame retardant for cable materials, whose raw materials include: 1500g of palygorskite clay, 150g of gamma-aminopropyltriethoxysilane, 300g of ethylenediamine, 800g of methyl acrylate, 300g of glyoxylic acid, and 1000g of hexagonal boron nitride with a particle size of 100-300nm.
[0082] The preparation method of the composite flame retardant for cable materials comprises the following steps:
[0083] S1, adding palygorskite clay to 10000g of deionized water, stirring at a speed of 1500r / min for 15min, treating with an ultrasonic pulverizer for 2.5h, the treatment power is 900W, adding γ-aminopropyltriethoxysilane, stirring at a temperature of 90°C for 90min, cooling to room temperature, filtering, and vacuum drying to obtain pretreated clay;
[0084] S2, adding the pretreated clay to 4000g methanol and stirring evenly, adding 5g potassium methoxide and stirring evenly, adding ethylenediamine and methyl acrylate in sequence under nitrogen protection, stirring at 15°C for 25h under nitrogen protection, heating to 35°C and stirring for 10h, removing nitrogen protection, adding 35% glyoxylic acid solution by mass, stirring at 15°C for 90min, centrifuging, washing with deionized water, and vacuum drying to obtain activated clay;
[0085] S3. Add hexagonal boron nitride and activated clay to 12000 g of 60% ethanol aqueous solution, reflux with stirring at 110° C. for 90 min, cool to room temperature, centrifuge, and vacuum dry.
[0086] A flame retardant cable material, the raw materials of which include: 1000g of polyethylene, 20g of polyolefin thermoplastic elastomer, and 250g of a composite flame retardant for the cable material.
[0087] The preparation method of the flame-retardant cable material comprises the following steps: uniformly mixing polyethylene, polyolefin thermoplastic elastomer and the composite flame retardant for the cable material, feeding into a double-roll mill, refining at a temperature of 140°C for 3 minutes, melting, plasticizing and molding at a temperature of 200°C for 3 minutes, the plasticizing pressure is 25MPa, and electron beam irradiation cross-linking is adopted, and the irradiation dose is 155kGy.
[0088] The tensile properties (tensile strength, elongation at break) of the flame-retardant cable materials obtained in Example 5 and Comparative Examples 1-2 were measured with reference to GB / T 1040.2-2022 "Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics", and the tensile speed was 50 mm / min. The flame-retardant cable materials obtained in Example 5 and Comparative Examples 1-2 were then subjected to heat aging (150°C × 72h), and then the tensile properties were measured, and the tensile property retention rate was calculated.
[0089] Tensile performance retention rate = tensile performance after heat aging / tensile performance before heat aging × 100%
[0090] like Figure 2 and Figure 3 As shown, the flame retardant cable material obtained in Example 5 has the highest tensile strength and the highest tensile property retention rate, which is better than that of Comparative Examples 1-2 (P < 0.05).
[0091] The thermal conductivity of the flame-retardant cable materials obtained in Example 5 and Comparative Examples 1-2 was measured with reference to GB / T 10294-2008 “Determination of Steady-State Thermal Resistance and Related Properties of Insulating Materials - Guarded Hot Plate Method”.
[0092] The oxygen index (LOI) of the flame retardant cable materials obtained in Example 5 and Comparative Examples 1-2 was measured with reference to GB / T 2406.2-2009 "Determination of combustion behavior of plastics by oxygen index method Part 2: Room temperature test".
[0093] like Figure 4 As shown, the thermal conductivity and oxygen index of the flame-retardant cable material obtained in Example 5 are the highest, which are better than those of Comparative Examples 1-2 (P < 0.05).
[0094] The flame retardant cable materials obtained in Example 5 and Comparative Examples 1-2 were graded and evaluated with reference to the vertical combustion test in GB / T 2408-2021 "Determination of combustion performance of plastics - horizontal and vertical methods". The flame retardant cable materials obtained in Example 5 were V-0, and the flame retardant cable materials obtained in Comparative Examples 1-2 were all V-1.
[0095] The applicant believes that the reason for the above results is that after the present invention pre-treats the palygorskite clay, a hyperbranched polyamide amine is combined on its surface, which can not only greatly enhance the dispersibility of the palygorskite clay in the polyethylene matrix, but also treat the end carboxylation with glyoxylic acid, and cooperate with the hyperbranched polyamide amine to have a unique cavity structure and three-dimensional structure, which is more conducive to the isotropic uniformity of the palygorskite clay in the polyethylene matrix, and the palygorskite clay can overlap in the polyethylene matrix to form a skeleton, and promote the formation of a new network, significantly improve the mechanical properties and flame retardant properties of the polyethylene matrix, and improve the durability of the cable material. The present invention uses hexagonal boron nitride after hydroxylation treatment, which can effectively increase the reactivity between hexagonal boron nitride and activated clay. The surface of the activated clay obtained by the present invention contains a large number of carboxyl groups, which can be combined with the hydroxyl groups on the surface of boron nitride. Not only is the bonding strength high, but also because of the special lamellar hexagonal structure of boron nitride, it can be evenly combined with the palygorskite clay structure. The two work synergistically, while improving the flame retardancy, the thermal conductivity is excellent.
[0096] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A composite flame retardant for cable materials, characterized in that: The raw materials include, by mass, 10-20 parts of palygorskite clay, 1-2 parts of gamma-aminopropyltriethoxysilane, 1.01-3.1 parts of sodium methoxide, 1-5 parts of ethylenediamine, 5-10 parts of methyl acrylate, 1.5-6 parts of glyoxylic acid, 1-2 parts of potassium ethoxide and 5-15 parts of hexagonal boron nitride.
2. The composite flame retardant for cable materials according to claim 1, characterized in that: The particle size of hexagonal boron nitride is 100-300nm.
3. A method for preparing the composite flame retardant for cable materials as claimed in claim 1 or 2, characterized in that: The steps include: S1. Add palygorskite clay to deionized water and stir for 10-20 min, perform ultrasonic grinding for 1-4 h, add γ-aminopropyltriethoxysilane, stir at 85-95° C. for 1-2 h, cool to room temperature, filter, and vacuum dry to obtain pretreated clay; S2, adding the pretreated clay to methanol and stirring evenly, adding potassium methoxide and stirring evenly, adding ethylenediamine and methyl acrylate in sequence under nitrogen protection, stirring at 10-20° C. for 20-30 hours under nitrogen protection, heating to 30-40° C. and stirring for 5-15 hours, removing nitrogen protection, adding glyoxylic acid solution, stirring at 10-20° C. for 1-2 hours, centrifuging, washing, and vacuum drying to obtain activated clay; S3. Mix and grind sodium methoxide and potassium ethoxide evenly, add hexagonal boron nitride, react at 180-190°C with stirring for 1-2h, cool to room temperature, wash, dry, add to ethanol aqueous solution with activated clay, reflux at 100-120°C with stirring for 1-2h, cool to room temperature, centrifuge, and dry in vacuo.
4. The method for preparing the composite flame retardant for cable materials according to claim 3, characterized in that: In S1, the ultrasonic pulverization treatment power is 800-1000W.
5. The method for preparing the composite flame retardant for cable materials according to claim 3, characterized in that: In S2, the mass fraction of the glyoxylic acid solution is 30-40%.
6. The method for preparing the composite flame retardant for cable materials according to claim 3, characterized in that: The mass ratio of potassium methoxide used in S2 to potassium methoxide used in S3 is 0.01-0.1:1-3.
7. The method for preparing the composite flame retardant for cable materials according to claim 3, characterized in that: In S3, the mass fraction of the ethanol aqueous solution is 50-70%.
8. A flame retardant cable material, characterized in that: The raw materials include: the composite flame retardant for cable materials as claimed in claim 1 or 2, and polyethylene.
9. The flame-retardant cable material according to claim 8, characterized in that: The raw materials include, by mass, 100 parts of polyethylene, 1-3 parts of a toughening agent, and 20-30 parts of the composite flame retardant for cable materials as claimed in claim 1 or 2.
10. A method for preparing the flame-retardant cable material according to claim 8 or 9, characterized in that: The method comprises the following steps: uniformly mixing polyethylene, a toughening agent and the composite flame retardant for cable materials as claimed in claim 1 or 2, refining at 130-150° C. for 1-5 minutes, melting, plasticizing and molding at 190-210° C. for 1-5 minutes, with a plasticizing pressure of 20-30 MPa, and crosslinking by electron beam irradiation with an irradiation dose of 150-160 kGy.
Citation Information
Patent Citations
Preparation method for palygorskite modified by PAMAM (polyamide-amine)
CN102153101A
Dendritic modified montmorillonite flame retardant and preparation method thereof
CN104710652A
Anti-aging and anti-tension flame-retardant polyethylene sheath material for refrigerator power line and making method of polyethylene sheath material
CN106084380A
Outdoor super-weather-resistant powder coating and preparation method thereof
CN112375455A
Attapulgite-loaded reinforced wood-plastic composite material and preparation method thereof
CN116445002A